Clinical Management of Vitamin A Responsive Dermatosis in a Labrador Retriever Dog - Sumathi, D.; Atmakur Venkatesh; K. Gopal; R. Rajalakshmi; K.R. Ravi; K. Mohanambal; K.K. Ponnuswamy (The Indian Veterinary Journal, 2026)
A five-year-old Labrador Retriever dog was presented to the Small Animal Medicine Unit, Veterinary College and Research Institute, Hospital Namakkal, with a history of recurrent skin lesions and mild pruritus for more than two years. The dog was active and alert with pink conjunctival mucous membrane and rectal temperature of 39.4ºC. Generalised dry crusty lesions, patchy alopecia, hyperkeratinization, and rancid fat odour were noticed on integumentary system examination. Haematology revealed leukocytosis with neutrophilia. Skin scrapings, tape impression technique and Wood’s lamp technique were negative for other skin infestations and infections. Abdominal ultrasonography revealed a normal spleen, liver and kidney. Histopathology of the skin showed no keratinization. Based on clinical examination and differential diagnosis for primary keratinization disorder, the animal was treated with Inj. Vitamin AD3E- 2ml along with supportive. Appropriate topical therapy was given. The skin lesions were cured rapidly and completely with vitamin A therapy, and the case was confirmed as a vitamin A-responsive dermatosis.